Implications for conifer glacial refugia and postglacial climatic variation in western Beringia from lake sediments of the Upper Indigirka basin. (31st March 2018) - Lozhkin, Anatoly; Anderson, Patricia; Minyuk, Pavel; Korzun, Julya; Brown, Thomas; Pakhomov, Alexander; Tsygankova, Valeriya; Burnatny, Sergei; Naumov, Alexey
Abstract : A c.  13 800 cal. a BP palynological record from Tschuch'ye Lake (eastern Yakutia), when combined with other palaeobotanical records from western Beringia, supports previous conclusions that Larix and Pinus pumila spread from multiple cryptic refugia during the Lateglacial period and middle Holocene, respectively. The antiquity and spatial distribution of Larix in many of these records suggest that full‐glacial landscapes probably had a small but important tree component. The Tschuch'ye record further indicates the absence of a Younger Dryas climatic reversal and is in accord with the preponderance of other data from western Beringia, which indicate warmer than present climates between c.  12 900 and 9100 cal. a BP. The subsequent spread of Pinus pumila, which has similar temperature requirements as Larix, denotes a shift to wetter but still warm climates during the middle Holocene, with palynological data suggesting optimal conditions in far western areas of western Beringia c.  7000–5000 cal. a BP. The postglacial occurrence of relatively warm/dry and warm/wet intervals is consistent with results of a regional climate‐model simulation that indicates warmer than present temperatures and decreased effective moisture at 11 000 cal. a BP and persistence of warm conditions but with greater moisture and longer growing season at 6000 cal. a BP.